The Role of Adaptive Leadership in Enhancing Employee Well-Being in Hybrid Work Environments: A Literature Review Post-Covid - Intan Ayu Marifath; Ratih Atma Faradila; Aldy Rostyawan (JOB: Journal of Organizational Behavior, 2025)
The global workforce's rapid transition to hybrid work models post-COVID-19 has highlighted both opportunities and significant challenges for employee well-being. This literature review systematically examines the role of adaptive leadership in enhancing employee well-being within these evolving environments. Utilizing a comprehensive search strategy across academic databases, studies published from 2020 onwards were analyzed to synthesize current knowledge. Findings indicate that adaptive leadership, characterized by fostering experimentation, promoting resilience, empowering employees, and maintaining a broad perspective, is crucial for navigating the complexities of hybrid work. The review concludes by emphasizing the imperative for organizations to develop adaptive leadership capabilities and proposes future research directions, including longitudinal studies and context-specific effectiveness analyses, to further understand and optimize employee well-being in hybrid work. Keywords: Hybrid Work, Adaptive Leadership, Employee well-being